Expanding the clinical and immunological phenotypes of PAX1-deficient SCID and CID patients - ÖZEN, AHMET OĞUZHAN (My University, 2023)
Paired box 1 (PAX1) deficiency has been reported in a small number of patients diagnosed with otofaciocervical syndrome type 2 (OFCS2). We described six new patients who demonstrated variable clinical penetrance. Reduced transcriptional activity of pathogenic variants confirmed partial or complete PAX1 deficiency. Thymic aplasia and hypoplasia were associated with impaired T cell immunity. Corrective treatment was required in 4/6 patients. Hematopoietic stem cell transplantation resulted in poor immune reconstitution with absent naïve T cells, contrasting with the superior recovery of T cell immunity after thymus transplantation. Normal ex vivo differentiation of PAX1-deficient CD34+ cells into mature T cells demonstrated the absence of a hematopoietic cell-intrinsic defect. New overlapping features with DiGeorge syndrome included primary hypoparathyroidism (n = 5) and congenital heart defects (n = 2), in line with PAX1 expression during early embryogenesis. Our results highlight new features of PAX1 deficiency, which are relevant to improving early diagnosis and identifying patients requiring corrective treatment.
Keywords: PAX1; Inborn errors of immunity; SCID; thymus; Otofaciocervical syndrome; Hypoparathyroidism